Evaluation of Learning Mathematics Economics and Business AE Class with Cipp Method - Larasati, Dorothea; Islami, Muhammad (Journal of Development Economic and Social Studies, 2025)
One of the subjects or courses that cannot be avoided from the faculty of economics and business is economic and business mathematics courses. Learning economic and business mathematics courses will not be separated from errors during the learning process. This study examines the evaluation of learning in economic and business mathematics courses in AE class from the aspects of CIPP method (context, input, process, and product). The research method used in this research is quantitative with collection techniques through questionnaires and observations. The population in this study came with 25 respondents. The data analysis technique used is descriptive quantitative. The results showed that the learning evaluation of economic and business mathematics courses in AE Class received the “Good” with a percentage of 81.2%. This research shows that AE class economics and business courses affect the learning of AE class economic and business mathematics from various aspects. This research is useful for educational institutions to improve the learning system at the university.